IS TODAY’S TEENAGER STRESSED? AN ANALYSIS BASED ON PSYCHODIAGNOSIS - Riffel, Carola Jorge; Vasconcelos, Cristiane; Silva, Arnislane Nogueira (Seven Editora, 2025)
This article aims to understand the main causes and symptoms that lead adolescents to demonstrate so much stress or anguish in the face of their daily lives, considering the performance of a psychological assessment as a tool to assist in this understanding. This study will be carried out through a literature review through searches of articles in databases, as well as books that address the subject. Adolescents marked by the transition to adulthood were found as results, who are faced with the failure of childhood ideals and the search for new cultures, a new group, in addition to their physical changes, their desires that were previously repressed and that are now reappearing. These transformations can cause stress, in addition to family and social relationships, daily and school factors, and pregnancy in girls. Thus, the adolescent can go through moments of stress and the psychological evaluation, with the battery of tests appropriate to the adolescent, can favor the treatment and understanding of the causes for stress in this phase. DOI: https://doi.org/10.56238/sevened2025.018-022